Islamic Religious Education Teacher’s Strategies in Improving Student’s Spirituality at SMP 2 Bendosari - Dara Amalia Thirafi; Triono Ali Mustofa (Journal of Educational Sciences, 2026)
Strengthening students' spirituality is an important challenge for Islamic religious education in the digital age, when the influence of social media, cultural changes, and a lack of family guidance often weaken students' religious awareness. This condition requires learning strategies that are more adaptive and relevant to the developmental needs of adolescents. This study aims to describe the strategies used by Islamic Religious Education teachers to enhance student spirituality, the forms of implementation in schools, as well as the impacts and obstacles that arise in its implementation. This study uses a qualitative approach with a case study design through observation, in-depth interviews, and documentation. Data analysis was conducted using an interactive model that included data reduction, data presentation, and conclusion drawing. The results showed that IRE teachers applied five main strategies, namely contextual learning, worship habits, role modeling, personal approaches, and collaboration with parents and schools. These strategies have been proven to increase student participation in religious activities, strengthen religious behavior, and encourage the internalization of Islamic values in daily life. However, the study also found obstacles such as differences in student motivation, the influence of digital media, and limited learning time.